SUSTAINABLE DEVELOPMENT ATTITUDE: A STUDY ON PERCEPTION AMONG PRIVATE & PUBLIC HIGHER LEARNING INSTITUTIONS STUDENT IN MALAYSIA - Zainordin, Nadzirah; Wahi, Wahida; Petrus, Magdalen; Koh, Chieng (MATTER: International Journal of Science and Technology, 2017)
The importance of sustainable development can be seen in many universities in Malaysia in establishing the syllabus and also an awareness on the concept itself among their students. The purposes of this study is to evaluate student’s perception on sustainable development concept and knowledge. The quantitative method has been choose where there are 300 numbers of questionnaire has been distributed and test to the respondents which actually there were comes from selected private and also public higher institutions. The overall findings reveal that even they are come from two different types of intuition but they are actually having the same perception towards sustainable development concept practising in their intuition. The weaknesses found in this study is a challenge to their intuition to provide clear picture on sustainable development concept and how they can react to achieve and well-implemented this concept in their institutions.